EFISIENSI PARASITISASI INANG SPODOPTERA LITURA (F.) OLEH ENDOPARASITOID SNELLENIUS MANILAE ASHMEAD DI LABORATORIUM - Endang Sri Ratna . (Universitas Lampung, 2008)
Eficiency of parasitization on larval host, Spodoptera litura (F.), by an endoparasitoid Snellenius (=Microplitis)manilae Ashmead in the laboratory. The armyworm, Spodoptera litura (F.) is the host of an endoparasitoid Snelleniusmanilae Ashmead. This research described the effect of host larval stage preference, the number of host exposure and theage of parasitoid on the resulting parasitization. Each group of the first to the fifth of host instar (30 larvae) was exposed for3 hours to a pair of four-day old parasitoids in a trial cage. The same exposures were conducted without choices by placingeach instar group within each trial cage. The parasitoid survival was observed by maintaining the parasitized larvae untiladult emergence. Each group of 10, 20, 30 and 40 of the second instar larvae were exposed for 12 hours/day to a matedfemale parasitoid. This experiment was conducted from the first day old parasitoid until the females died. The percentageof parasitization, superparasitization, oviposition and the fecundity of adults were recorded. Each group of thirty secondinstar larvae was exposed separately to a mated female parasitoid of 1 to 9 days old. The survival of progeny was recorded.All treatments in this observation were repeated 10 times. S. manilae preferred to lay eggs on the third (41.7%) followed bythe second (22.3%) instar larvae of S. litura. The lowest percentages of superparasitization obtained from the first and thesecond instar larvae were between 11 and 15% and the highest percentage of superparasitization obtained from the fourthinstar larvae was 52%. The highest survival of parasitoid was found on the exposure of the second instar larvae whichreached 16%. The highest efficiency of parasitism (80.9%) was found on the twenty of the second instar larval exposuredensity which produced 59% of optimal parasitization level, the average rate of egg laid by females was 25 eggs/day, andthe fecundity was 185 eggs/female. Female parasitoids of 1-7 days old gave the same opportunity to produce progenysurvival which was in the range of 10.3-25.7%.